2002
DOI: 10.3327/jnst.39.778
|View full text |Cite
|
Sign up to set email alerts
|

Development of 9Cr-ODS Martensitic Steel Claddings for Fuel Pins by means of Ferrite to Austenite Phase Transformation.

Abstract: For use as fuel cladding of liquid metal fast reactors, Fe-0.12C-9Cr-2W ODS martensitic steel claddings were developed by cold-rolling under the softened ferrite phase induced by slow cooling from austenite phase, subsequently by ferrite to austenite phase transformation to break up substantially elongated grains produced by cold-rolling at the final heat-treatment. The produced claddings showed noticeable improvement in tensile and creep rupture strength that are considerably superior to PNC-FMS and even aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 16 publications
2
80
0
Order By: Relevance
“…9Cr-1Mo steel, PNC-FMS and so on. 1,2) It is widely recognized that these desirable properties are attributable to nano-size Y-Ti-O complex oxide particles dispersed in the matrix which act as obstacles to movement of dislocations. A high density of nano-size YTi-O complex oxide particles is produced by mechanically alloying (MA) Fe-Cr-Ti powders with Y 2 O 3 followed by hot-solidification process.…”
Section: Introductionmentioning
confidence: 99%
“…9Cr-1Mo steel, PNC-FMS and so on. 1,2) It is widely recognized that these desirable properties are attributable to nano-size Y-Ti-O complex oxide particles dispersed in the matrix which act as obstacles to movement of dislocations. A high density of nano-size YTi-O complex oxide particles is produced by mechanically alloying (MA) Fe-Cr-Ti powders with Y 2 O 3 followed by hot-solidification process.…”
Section: Introductionmentioning
confidence: 99%
“…2,3) It was recently shown that microstructure and creep strength of 9CrODS steel is sensitive to subtle changes of oxygen and titanium concentrations. 3,4) To develop a consistently reliable manufacturing procedure for high strength 9CrODS steel, it is important to clarify the effects of manufacturing conditions on the mechanical properties of 9CrODS steel.…”
Section: Introductionmentioning
confidence: 99%
“…These powders were degassed in vacuum, sealed in mild-steel cans, and consolidated by hot extrusion at 1423 K. From these consolidated bars, tubes were manufactured by a six-pass warm rolling at 923-973 K for 1DS and 1DK, and a two-pass spiral cold rolling for M93, F94 and F95 with intermediate and final heat treatments. 3,4) The chemical compositions and heat treatment conditions of the ODS ferritic and martensitic steels are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%